A level of service method for evaluating A.S.R.S. based on users experience - Sallahudin, Mohd. Faez Shukri (2017)
The Automated Storage and Retrieval System or known as ASRS is an automated system where it was invented over the century with considerations of high ability to overcome various problems exists within the warehouse operations. However, to interpret the effectiveness of the ASRS quality system, it is difficult since a detail of study for evaluating the ASRS toward the entire operation of the system was not found. As the main objective of this research is to identify factors that may affect the ASRS quality of service, this study has aim for evaluating the ASRS based on two basic criteria according to the global view into current adoption warehouse. The criteria identified then subsequently incorporated into each statement of questionnaire for distribution to current warehouse’s workers. Data obtained from the results of a survey distributions to respondents who has experiences to operates this system is useful for evaluation the ASRS based on their expectations and perceptions toward ASRS service quality. The data collected then will be analysed and calculated through proposed model. Next, the results received from each factor will be suited based on rating system to representing the existing services of ASRS quality which consisted by six stages of point system. This grading is consisted by highest ranking of LOS A which shown "the highest quality system" until to the lowest ranking of LOS F that was representing "this system does not acceptable ". The average of the results toward the usage of ASRS on current adopted warehouse has found and it was placed on the highest quality level. Nevertheless, there are several factors that must be emphasized by warehouse management or any research to improve the quality of services through the extensive findings on the lowest dimension stated on this study for giving fully satisfaction and enhance user requirements and needs. Hopefully, the findings and recommendations given through this method could be used as a measuring tool for comparing the performance of various storage systems that exist around the world.